The impact of climate vulnerability on firms’ cost of capital and access to finance - Kling, Gerhard; Volz, Ulrich; Murinde, Victor; Ayas, Sibel (World development, 2021)
•First systematic investigation of the effect of climate vulnerability on firms’ cost of capital and access to finance.•Theoretically, shows how climate vulnerability could affect firms’ cost of capital and access to finance.•Constructs new climate vulnerability index and uses panel instrumental variable regressions to address endogeneity problems.•Use of comprehensive firm-level data in panel data regressions and structural equation models.•Sheds light on a hitherto under-appreciated cost of climate change for climate vulnerable developing economies. This article presents the first systematic investigation of the effects of climate-related vulnerability on firms’ cost of capital and access to finance and sheds light on a hitherto under-appreciated cost of climate change for climate vulnerable developing economies. We first show theoretically how climate vulnerability could affect firms’ cost of capital and access to finance. Apart from a possible impact on cost of debt and equity, which drive cost of capital, firms in countries with high exposure to climate risk might be more financially constrained. The latter results in low levels of debt relative to total assets or equity due to restricted access to finance. We then examine this issue empirically, using panel data of 15,265 firms in 71 countries over the period 1999–2017. We invoke panel data regressions and structural equation models, with firm-level data from the Thomson Reuters Eikon database and different measures of climate vulnerability based on the ND-GAIN climate vulnerability index. We construct a new climate vulnerability index and use panel instrumental variable regressions to address endogeneity problems. Our empirical findings suggest that climate vulnerability increases cost of debt directly and indirectly through its impact on restricting access to finance. However, we find limited evidence that climate vulnerability affects cost of equity. Our estimations suggest that the direct effect of climate vulnerability on the average increase in cost of debt from 1991 to 2017 has been 0.63%. In addition, the indirect effect through climate vulnerability’s impact on financial leverage has contributed an additional 0.05%.